Analysis of the Role of Perum Bulog in Maintaining the Stability of the National Rice Supply Chain - Shofia Rofifah Azhaara; Yulianah Yulianah; Elsa Rosmiati Alisa; Tri Ceysha Nur Wahyuni; Sulaiman Ar Rasyid Al Khoirullahu (Advances: Jurnal Ekonomi & Bisnis, 2026)
Purpose: This study aims to analyze the role of Perum BULOG in maintaining the stability of Indonesia’s rice supply chain and to identify operational constraints affecting distribution effectiveness and food price stabilization. Research Method: This study employed a descriptive qualitative approach using semi-structured interviews, field observations, and secondary data from BULOG annual reports, BPS statistics, and food policy regulations. Data were analyzed through interactive qualitative analysis involving data reduction, presentation, and conclusion verification. Results and Discussion: The findings indicate that Perum BULOG contributes to rice supply chain stability through Government Rice Reserves (CBP), domestic rice procurement, SPHP market intervention, food aid distribution, equitable distribution systems, and logistics modernization. However, operational effectiveness remains constrained by infrastructure disparities, transportation barriers, warehousing limitations, and institutional coordination challenges across regions. Implications: The study highlights the importance of strengthening logistics governance, digital distribution systems, and inter-agency coordination to improve supply chain responsiveness and regional food accessibility. Originality: This study provides an operational and supply chain governance perspective in evaluating BULOG’s role beyond normative policy discussions.